GUGATAN PERBUATAN MELAWAN HUKUM YANG DILAKUKAN OLEH MANTAN REKTOR YANG DI BERHENTIKANSEBELUM MASA JABATAN BERAKHIR(Studi Putusan Nomor: 2/Pdt.Sus-PHI/2023/PN Tjk) - Kris Chandra Aldyanto; I Ketut Seregig, Yulia Hesti (INTELIGENSIA MEDIA, 2024)
Indonesia is a legal state, which contains all kinds of rules to improve the welfare of society. Indonesian citizens to fulfill their daily living needs by working. The fields of work in Indonesia are very diverse, ranging from farmers, fishermen, factory workers and so on. Recently there was a problem in Indonesia with the outbreak of the Covid-19 disease, which had many impacts on the citizens of the country, one of which was the economy. At that time, there were massive layoffs from entrepreneurs to their workers, giving rise to increased unemployment and poverty in Indonesia. During layoffs, many employees also file a lawsuit against their workplace to obtain justice in terms of severance pay, or work wages. This continues to happen to this day, there are still many entrepreneurs who behave abusively towards their employees so that many employees are fighting against the law.